Analisis Faktor-Faktor yang Berhubungan dengan Kejadian Hipertensi pada Usia 30-59 Tahun Puskesmas Kebomas - Zufra Inayah; Dini Setiyo Rini; Agnes Faiqotun Ni’mah (Journal of Educational Innovation and Public Health, 2026)
Hypertension is included in the group of non-communicable diseases and is a world health issue with a fairly high mortality rate. Individuals can be considered to have hypertension if their blood pressure rises above the standard limit, which is above 140/90 mmHg. The study was conducted to examine factors such as diet, physical activity, and family history with the incidence of hypertension at the age of 30-59 years at the Kebomas Health Center. The number of hypertensive patients in health centers is quite high and every year it increases so researchers want to conduct research to find out more about hypertension. The methods used are quantitative and cross-sectional design. The population and samples were taken from patients who visited the Kebomas Health Center within 3 days who met the criteria of 80 respondents. The sampling technique uses purposive sampling and chi square test to analyze the data. This study obtained a significant association with significant family history factors of <0.001, significant dietary level <0.001 and significant physical activity level 0.015 with the incidence of hypertension at the age of 30-59 years at the Kebomas Health Center, and hypertension patients are encouraged to check blood pressure consistently so that it can be controlled and do not cause other side effects and the health center is expected to be able to provide promotive and preventive services to patients hypertension.